Penerapan Teknik Forgiveness Therapy Untuk Mengatasi Rasa Dendam - Apriliadi, Duta Duta Apriliadi (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2024)
Abstrac: This research is entitled Application of Forgiveness Therapy Techniques to Overcome Resentment (Case Study of Client “D” in Talang Ubi, PALI District). The purpose of this study is to find out how the image of revenge for client “D” in Talang Ubi, PALI Regency, is then to eliminate this feeling of resentment towards the person who bullied him by applying forgiveness therapy techniques. In this study the authors used a type of field research, a qualitative approach, and used the case study method. The subject of this research is client D as the primary data source, then his mother and friends as the secondary data source. Data collection tools in this study are observation, interviews and documentation. Qualitative data analysis techniques consist of three stages, namely pattern matching, explanation making and time series analysis. The results of this study indicate that client D, a teenager who has intellectual limitations, becomes a victim of bullying so that client D holds an excess of revenge against the person who bullied him and wants to avenge him. Therefore, by applying forgiveness therapy techniques, it is hoped that client D will fully forgive and let go of other people's mistakes so that unwanted bad things don't happen.Keywords: Revenge, Forgiveness Therapy Techniques, Bullying